Geometrielernen digital unterstützen - Räumliche Kompetenzen und individuelle Lernwege mittels adaptierbarer algorithmischer Rückmeldemöglichkeiten fördern - Bechinie, Dominik; Eilerts, Katja; Huhmann, Tobias; Lenke, Michael; Schulte, Carsten; Winkelnkemper, Felix (Beiträge zum Mathematikunterricht 2021)

Nutzung der Personas-Methode zum Umgang mit der Heterogenität von Informatik-Studierenden - Gerstenberger, Dietrich Karl-Heinz; Winkelnkemper, Felix; Schulte, Carsten (9. Fachtagung Hochschuldidaktik Informatik (HDI))

Zur neuen Bedeutung von Daten in Data Science und künstlicher Intelligenz - Höper, Lukas; Podworny, Susanne; Hüsing, Sven; Schulte, Carsten; Fleischer, Yannik; Biehler, Rolf; Frischemeier, Daniel; Malatyali, Hülya (19. GI-Fachtagung Informatik und Schule, INFOS 2021, Wuppertal, Germany, September 8-10, 2021)

Entwicklung und Rekonstruktion einer interaktionsgeprägten Sichtweise auf das komplementäre Mensch-Maschine-Verhältnis - Budde, Lea

Computers and Education – Recognising Opportunities and Managing Challenges - Passey, Don; Brinda, Torsten; Cornu, Bernard; Holvikivi, Jaana; Lewin, Cathy; Magenheim, Johannes; Morel, Raymond; Osorio, Javier; Tatnall, Arthur; Thompson, Barrie; Webb, Mary (Advancing Research in Information and Communication Technology)
Keywords: Educational technologies; Education and technologies; Digital technologies and education; Information technologies; Communication technologies; Educational technologies and research; Educational technologies and pedagogical practices; Educational technologies and policy; Educational management and technologies; Professional development and educational technologies

Data Science ab Klasse 5–Konkrete Unterrichtsvorschläge für künstliche Intelligenz unplugged und Datenbewusstsein - Podworny, Susanne; Höper, Lukas; Fleischer, Yannik; Hüsing, Sven; Schulte, Carsten (INFOS 2021–19. GI-Fachtagung Informatik und Schule)

Zur neuen Bedeutung von Daten in Data Science und künstlicher Intelligenz - Höper, Lukas; Podworny, Susanne; Hüsing, Sven; Schulte, Carsten; Fleischer, Yannik; Biehler, Rolf; Frischemeier, Daniel; Malatyali, Hülya (INFOS 2021–19. GI-Fachtagung Informatik und Schule)

Faszination 3D-Film: Entwicklung einer 3D-Konstruktion - Hüsing, Sven; Weiser, Niklas; Biehler, Rolf (mathematik lehren)

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Der Darstellungsflüchtigkeit im Geometrieunterricht durch digitale Unterstützung entgegenwirken - Huhmann, Tobias; Eilterts, Katja; Schulte, Carsten; Winkelnkemper, Felix (Digitales Lernen in der Grundschule II: Aktuelle Trends in Forschung und Praxis)

The Interdisciplinary Development of an Educational Game for Primary School Children--Lessons Learned - Winkelnkemper, Felix; Schulte, Carsten; Eilerts, Katja; Bechinie, Dominik; Huhmann, Tobias (EdMedia+ Innovate Learning)

Combining Ideas and Artifacts: An Interaction-Focused View on Computing Education Using a Cybersecurity Example - Terfloth, Lutz; Budde, Lea; Schulte, Carsten
In this paper, we present a novel approach to design teaching interventions for computing education, elaborated using an example of cybersecurity education. Cybersecurity education, similar to other computing education domains, often focuses on one aspect and separate themselves from the other approach. In other words, they focus on one of the two different aspects: a) either teaching how to use and to behave, or b) how technology works. Here we suggest another point of focal awareness for teaching – interaction – that allows the recombination of both approaches in a novel way, leading to a reconstruction of the teaching and learning content in a way that – as we hope – supports an understanding on a higher level and thus gives the chance to better develop agency. For this didactic reconstruction of teaching content, we use an approach called the hybrid interaction system framework. In cybersecurity training, teaching interventions oftentimes are in a way successful but seem to not lead to long-lasting changes towards secure behavior. Using simply password security as an example, we show how this new approach recombines the two different priory mentioned teaching approaches in a novel way. Within this short paper, we present our current research progress, discuss potentials and values of the approach in general, and by way of example. Our intention of this submission and early disclosure is to spark discussion and generate further insights especially regarding the following question: What implications does the hybrid interaction system approach have on learning scenarios?

Machine learning for human learners: opportunities, issues, tensions and threats - Webb, Mary E; Fluck, Andrew; Magenheim, Johannes; Malyn-Smith, Joyce; Waters, Juliet; Deschênes , Michelle; Zagami, Jason (Educational Technology Research and Development)

< Big Data> aus der Perspektive von Informatischer Bildung und Medienpädagogik - Magenheim, Johannes (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)

Data science education - Magenheim, Johannes; Schulte, Carsten (Encyclopedia of Education and Information Technologies. Cham: Springer)

Programmieren - Lehren und Lernen mit und über Medien - Schulte, Carsten; Budde, Lea; Winkelnkemper, Felix (Mobile Medien im Schulkontext)

Data Science und Big Data in der beruflichen Bildung – Konzeption und Erprobung eines Projektkurses für die Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael (Sammelband der 27. Fachtagung der BAG Berufliche Bildung)
Die Themen „Big Data“, „Künstliche Intelligenz und „Data Science“ werden seit einiger Zeit nicht nur in der breiten Öffentlichkeit kontrovers diskutiert, sondern stellen für die Ausbildung in den IT- und IT-nahen Berufen schon heute neue Herausforderungen dar, die in Zukunft durch die gesellschaftliche und technologische Weiterentwicklung hin zu einer Datengesellschaft noch größer werden. An dieser Stelle stellt sich die Frage, welche Aspekte dieses großen Themenkomplexes für Schule und Ausbildung von Wichtigkeit sind und wie diese Themen sinnstiftend und gewinnbringend in die informatische Ausbildung in verschiedenen Bildungsgängen integriert werden können. Im Rahmen des von uns im Jahr 2017 organisierten Symposiums zum Thema „Data Science“ wurden für die Bildung relevante Aspekte erörtert, wodurch als Kernelemente für den Unterricht Algorithmen der Künstlichen Intelligenz und ihre Anwendung in Industrie und Gesellschaft, Explorationen von Big Data sowie der Umgang mit eigenen Daten in sozialen Netzwerken herausgearbeitet wurden. Ziel ist, aus diesen Themenbereichen sowohl ein umfassendes Curriculum als auch Module für verschiedene Unterrichtsszenarien zu entwickeln und zu erproben. Durch diese Materialien soll es Lehrkräften aus der Informatik, Mathematik oder Technik ermöglicht werden, diese Themen auf Basis des Curriculums und der erprobten Unterrichtskonzepte selbst zu unterrichten. Hierfür wurde im Rahmen des Projekts ProDaBi (Projekt Data Science und Big Data in der Schule, https://www.prodabi.de), initiiert von der Telekom Stiftung, ein experimenteller Projektkurs entwickelt, den wir mit Schüler:innen der Sekundarstufe II an der Universität Paderborn im Schuljahr 2018/19 durchführten. Dieser Kurs enthält neben einem Modul zur Exploration von Big Data und einem weiteren Modul zum Maschinellen Lernen als Teil der Künstlichen Intelligenz auch eine Projektphase, die es in Zusammenarbeit mit lokalen Unternehmen den Schüler:innen ermöglicht, das Erlernte in ein reales Data Science-Projekt einzubringen. Aus den Erfahrungen dieses Projektkurses sowie den parallel durchgeführten Erprobungen einzelner Bausteine auch mit beruflichen Schulen werden ab dem Schuljahr 2019/20 die hierfür verwendeten Materialien weiterentwickelt und weiteren Kooperationspartnern zur Erprobung zur Verfügung gestellt. Damit wurden zum Ende des Projekts nicht nur vollständige Unterrichtsmaterialien, sondern auch ein umfassendes Curriculum entwickelt.
Keywords: Berufsbildung; vocational education; Ausbildung; training; berufliche Weiterbildung; advanced vocational education; Digitalisierung; digitalization; Unterricht; teaching; Lehrmethode; teaching method; Interdisziplinarität; interdisciplinarity; Fachdidaktik; subject didactics; Curriculum; curriculum; gewerblich-technischer Beruf; vocational/technical occupation; Fachkraft; specialist; Qualifikationsanforderungen; qualification requirements; Kompetenz; competence; Lehrerbildung; teacher training; Bundesrepublik Deutschland; Federal Republic of Germany

Understanding and Explaining Digital Artefacts - the Role of a Duality (Accepted Paper - Digital Publication Follows) - Budde, Lea; Schulte, Carsten; Buhl, Heike M.; Muehling, Andreas (Seventh International Conference on Learning and Teaching in Computing and Engineeringe)
Keywords: ⛔ No DOI found

Data science education in secondary schools: Teaching and learning decision trees with CODAP and Jupyter Notebooks as an example of integrating machine learning into statistics education - Biehler, Rolf; Fleischer, Yannik; Budde, Lea; Frischemeier, Daniel; Gerstenberger, Dietrich; Podworny, Susanne; Schulte, Carsten (New Skills in the Changing World of Statistics Education Proceedings of the Roundtable conference of the International Association for Statistical Education (IASE))

Data Science Education in Secondary School: How to Develop Statistical Reasoning When Exploring Data Using CODAP - Budde, Lea; Frischemeier, Daniel; Biehler, Rolf; Fleischer, Yannik; Gerstenberger, Dietrich; Podworny, Susanne; Schulte, Carsten (New Skills in the Changing World of Statistics Education: Proceedings of the Roundtable conference of the International Association for Statistical Education (IASE), July 2020)